Administrative Possibilities of Academic Institutions and Their Correlation with Sports Tendencies of Students and Attitudes towards Practicing Sports - Salam Hantosh Rashed (Journal of Global Pharma Technology, 2016)
The research aims to identify the availability of the administrative possibilities of academic institutions, sports and their correlation with the wishes and preferences of students, the sample included current research (367) students were chosen randomly stratified where they were taking the sample from the Department of Physical Education and Sports Science for the academic year (2017/2018), where the researchers developed a questionnaire consisting of (3) areas and (20) is distributed when the sample data analysis was used arithmetic averages and standard deviations using the bag statistical (SPSS). The most important results of the research, most sports establishments in the department of physical education and sports sciences neglected, as well as there is no supervisor for every sport activity of the programs of sports in the department of physical education and Sports sciences. There is no fitness related to health because of the lack of sports activities in the department of physical education and sports sciences, and the most important recommendations: The head of the department of Physical Education and Sports Sciences must provide all possibilities for students to exercise sports activities, and must provide supervisors of various activities for students in all disciplines and sports activities, and provide effective administrative possibilities through interest in the institutions of the department of physical education and mathematical sciences.Keywords: Administrative possibilities, Sports tendencies and practicing sports.